2016
DOI: 10.1186/s12963-016-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes detection and management among insured adults

Abstract: BackgroundThe Centers for Disease Control and Prevention estimates that 28.9 million adults had diabetes in 2012 in the US, though many patients are undiagnosed or not managing their condition. This study provides US national and state estimates of insured adults with type 2 diabetes who are diagnosed, receiving exams and medication, managing glycemic levels, with diabetes complications, and their health expenditures. Such information can be used for benchmarking and to identify gaps in diabetes detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
2
29
1
Order By: Relevance
“…Although type 2 diabetes is generally regarded to account for 90-95% of diabetes cases,1 the International Diabetes Federation reported that approximately 87-91% of people with diabetes in high income countries have type 2 diabetes, 7-12% have type 1 diabetes, and 1-3% have other diabetes subtypes 34. One study in the United States using medical claims data estimated that type 2 diabetes accounted for about 92% of cases of diabetes among insured US adults, although the results could not be generalized to the US population 35. The proportion of type 2 diabetes in cases of diagnosed diabetes in the present study (91.2%), based on the most recent prevalence estimates in 2016 and 2017, was comparable to the previously reported prevalence.…”
Section: Discussioncontrasting
confidence: 67%
“…Although type 2 diabetes is generally regarded to account for 90-95% of diabetes cases,1 the International Diabetes Federation reported that approximately 87-91% of people with diabetes in high income countries have type 2 diabetes, 7-12% have type 1 diabetes, and 1-3% have other diabetes subtypes 34. One study in the United States using medical claims data estimated that type 2 diabetes accounted for about 92% of cases of diabetes among insured US adults, although the results could not be generalized to the US population 35. The proportion of type 2 diabetes in cases of diagnosed diabetes in the present study (91.2%), based on the most recent prevalence estimates in 2016 and 2017, was comparable to the previously reported prevalence.…”
Section: Discussioncontrasting
confidence: 67%
“…Medicaid, as the primary health insurance program for low-income people in the US, covered about 8% of all individuals with diagnosed diabetes in 2009 (approximately 1.8 million adults) [1,2]. In 2012, nearly 13% of total healthcare expenditures for diabetes was provided by Medicaid (~$28 billion) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, nearly 13% of total healthcare expenditures for diabetes was provided by Medicaid (~$28 billion) [3]. For each Medicaid enrollee with T2DM, the age-adjusted annual medical cost was $14,170 in 2012, higher than $9,560 in those with commercial insurance [1], with the annual medical cost increasing to $17,830 for those with a diagnosis code of uncontrolled diabetes (HbA1c > 9%) possibly due to a higher prevalence of diabetes complications [1]. Of Medicaid enrollees with T2DM, only 64% received annual HbA1c test and even a lower portion (58%) had controlled diabetes in 2012 [1].…”
Section: Introductionmentioning
confidence: 99%
“…That it can remain asymptomatic for several years contributes to this burden by allowing complications associated with it to accumulate that could be avoided were it detected and managed earlier [8,10,34]. While prompt identification and effective management are clearly important to avoiding such costs, several studies highlight not only the existence of a substantial prevalence of undiagnosed disease [4,14,17,20,28,32] but also the existence of distinct patterns of undiagnosed disease. In the UK, Moody et al [20], for example, found that males, those who are older (greater than 34 years) and those who are ethnic Asians were more likely to have undiagnosed diabetes.…”
Section: Introductionmentioning
confidence: 99%